Analysis of the influence of price, e-service quality and user decisions on user loyalty of online transportation services and e-wom as a mediation - Nugroho, Rizki Irman; Sampurna, Dian Surya (Jurnal Riset Manajemen dan Bisnis, 2024)
This research aims to examine the influence of price, e-service quality, user decisions on loyalty and e-WOM as mediation. The strategy used in this research is using an associative research strategy. Associative research is a research problem formulation that asks about the relationship between two or more variables. In this research, an associative research strategy is used to identify the influence of variables As well as Variable Z, namely E-WOM in mediation (intervening variable). The research results prove that (1) Price has an effect on E-WOM, (2) Price has an effect on Loyalty, (3) E-Service Quality has an effect on E-WOM, (4) E-Service Quality has an effect on loyalty, (5) User Decisions influence E-WOM, (6) User Decisions influence Loyalty, (7) E-WOM influences Loyalty, (8) E-WOM mediates the influence of Price on Loyalty, (9) E -WOM mediation the influence.